Digital Transformation of Msmes And Its Contribution To Economic Performance Toward Indonesia Emas 2045 - Hutabarat, Sinta Veronika; Windari, Furi; Wardina, Heni; Hanum, Rahmadiah (Jurnal Mantik, 2026)
Digital transformation is a critical factor in strengthening micro, small, and medium enterprises (MSMEs) to support sustainable economic growth. This study aims to analyze the contribution of MSME digital transformation to economic performance within the perspective of Indonesia Emas 2045. The research adopts a quantitative approach using survey data collected from MSME actors who have implemented digital technologies in their business operations. Data are analyzed using multiple linear regression to examine the influence of digital marketing, digital payment systems, and online marketplaces on MSME economic performance. The findings indicate that digital transformation significantly improves MSME competitiveness, sales growth, and operational efficiency. This study contributes to the economic development literature by positioning MSME digitalization as a strategic driver for achieving Indonesia’s long-term national development vision. The results provide policy implications for accelerating MSME digital adoption to support inclusive and sustainable economic growth.